COMMUNICATING WITH THE MEDIA. PERSPECTIVES ON AN EMERGING DIGITAL NEWS INDUSTRY - NISTOR, Cristina (Presa Universitară Clujeană, 2016)
Over the last two decades media organizations and professional communication have stepped into the fascinating, dynamic and stimulating realm of the Internet that has challenged them to understand the new cyber‐geography, later to identify the new media consumers and, furthermore, to structurally redesign, again and again, news stories, media strategies and communication policies. In the new technological framework everybody can communicate and at the same time the availability and variety of information has expanded so that the boundary between good quality and poor quality information has become blurred (Krimsky, 2007).